Investigation of the influence of hardness characteristics of the collet-part lathe system - Alrefo, Ibrahim Farhan Salman; Alnusirat, Walid Ibrahim; Litvin, Оleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
The results of the study of the hardness characteristics of the collet-part lathe system, which are essentially nonlinear and influence the damping parameters of the spindle assembly unit, are presented. The aim of the work is to study the characteristics of the nonlinear hardness of the elements of the collet-part technological system. In order to realize this aim, in the course of experimental research, static and dynamic characteristics of the spindle core hardness are defined, which are looped hysteresis curves that are characteristic of mechanical systems with a large number of bonds. Measurements of nonlinear parameters of the hardness of the collet-part system are carried out. Measurements are made according to the original method. The basis of the technique is the multi-cycle static load of the spindle in the processing zone in the direction of the vector of the dynamic component of the cutting force by the developed equipment. The equipment includes a screw loader, a two-way ring dynamometer and a mandrel fitted in the spindle of the machine. As a result of the research, the features of the nonlinear characteristics of the hardness of the collet-part lathe system are determined. For the collet-part system, the width of the hysteresis loop in the cold state can reach 20...70 microns. The hysteresis characteristics of the collet-part system in the heated state have the width of the hysteresis loop of 50...200 microns with clamping the part with a diameter of 80...115 mm and a radius of 100...120 mm. Recommendations on the assessment of the hardness change limit depending on the design of the collet are developed. The proposed technique allows one cartridge position to be measured by pressing according to the scheme of loading «on a cam» and «between cams», which reduces twofold the amount of experimental research.